On almost p-bounded variation of lacunary sequences - Karakaya, Vatan; Savas, Ekrem (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this work, we generalize the lacunary almost bounded variation sequence spaces to lacunary almost p-bounded variation sequence spaces. Also some topological results and inclusion relations of such spaces have been discussed. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Paranormed space; Lacunary sequences; Almost convergence; Almost bounded variation; Mathematics